DINAMIKA KANDIDASI PARTAI POLITIK PADA PEMILIHAN KEPALA DAERAH DI PROVINSI RIAU TAHUN 2017-2018 (Studi : Pasangan Syamsuar dan Edi Afrizal Natar Nasution) - Ahmad Romadan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted with the aim to find out the Dynamics of Candidation that occurred in the regional head elections in Riau Province in 2017-2018 in particular was the dynamics of candidacy of the pair Syamsuar and Edi Afrizal Natar Nasution in obtaining the support of the Polytic Party. The main problem in this research is in the process of candidacy of the National Mandate Party, the Prosperous Justice Party, and the National Democratic Party due to the election of party external cadres to be promoted to become candidates for regional heads. This study uses descriptive analytical methods with a type of qualitative research. The type of data used in this study are primary data and secondary data obtained through direct interviews with informants who are considered to know and understand the problems in the field.Based on the explanation above, it can be concluded that in the selection process of candidates by several political parties in Riau Province, it can be concluded that the candidate screening model can be said as having an Inclusive model. In the process of who selecting candidates some political parties are said to be political parties. has an exclusive model, while in the process of explaining where the dominant candidates are selected then from several political parties using the centralized method, and in the process of determining candidates made by several political parties to determine the candidates to be carried by the party the party uses the election model that was carried out by the elite of the central party of the political party concerned.In addition, there are dynamics of candidation that occur when political parties cannot prepare their party's internal cadres in the selection process of candidates to face political contestation. Then the party's external cadres who have better abilities than the internal party cadres will take the opportunity and get support to represent the political party.Keywords: Candidacy, Political Parties,Dynamics